Emerging microfluidic technologies for microbiome research - Yu, Yue; Wen, Hui; Li, Sihong; Cao, Haojie; Li, Xuefei; Ma, Zhixin; She, Xiaoyi; Zhou, Lei; Huang, Shuqiang (Frontiers in Microbiology, 2022)
The importance of the microbiome is increasingly prominent. For example, the human microbiome has been proven to be strongly associated with health conditions, while the environmental microbiome is recognized to have a profound influence on agriculture and even the global climate. Furthermore, the microbiome can serve as a fascinating reservoir of genes that encode tremendously valuable compounds for industrial and medical applications. In the past decades, various technologies have been developed to better understand and exploit the microbiome. In particular, microfluidics has demonstrated its strength and prominence in the microbiome research. By taking advantage of microfluidic technologies, inherited shortcomings of traditional methods such as low throughput, labor-consuming, and high-cost are being compensated or bypassed. In this review, we will summarize a broad spectrum of microfluidic technologies that have addressed various needs in the field of microbiome research, as well as the achievements that were enabled by the microfluidics (or technological advances). Finally, how microfluidics overcome the limitations of conventional methods by technology integration will also be discussed.